Transcriptomic signatures of classical monocytes reveal pro-inflammatory modules and heterogeneity in polyarticular juvenile idiopathic arthritis - Hounkpe, Bidossessi W.; Sales, Lucas P.; Ribeiro, Surian C. R.; Perez, Mariana O.; Caparbo, Valéria F.; Domiciano, Diogo Souza; Figueiredo, Camille P.; Pereira, Rosa M. R.; Borba, Eduardo F. (Frontiers in Immunology, 2024)
Introduction: Polyarticular Juvenile Idiopathic Arthritis (pJIA) is a childhood-onset autoimmune disease. Immune cells contribute to persistent inflammation observed in pJIA. Despite the crucial roleof monocytes in arthritis, the precise involvement of classical monocytes in the pathogenesis of pJIA remains uncertain. Here, we aimed to uncover the transcriptomic patterns of classical monocytes in pJIA, focusing on their involvement in disease mechanism and heterogeneity. Methods: Seventeen healthy subjects and eighteen premenopausal women with pJIA according to ILAR criteria were included. Classical monocytes were isolated and RNA sequencing was performed. Differential expression analysis was used to compare pJIA patients and healthy control group. Differentially expressed genes (DEGs) were identified and gene set enrichment analysis (GSEA) was performed. Using unsupervised learning approach, patients were clustered in two groups based on their similarities at transcriptomic level. Subsequently, these clusters underwent a comparative analysis to reveal differences at the transcriptomic level. Results: We identified 440 DEGs in pJIA patients of which 360 were up-regulated and 80 downregulated. GSEA highlighted TNF- and IFN- response. Importantly, this analysis detected genes targeted by pJIA therapy, but also identified new modulators of immuno-inflammation. PLAUR, IL1B, IL6, CDKN1A, PIM1 and ICAM1 were pointed as drivers of chronic hyperinflammation. Unsupervised learning approach revealed two clusters within pJIA, each exhibiting varying inflammation levels.These findings indicate the pivotal role of immuno-inflammation driven by classical monocytes in pJIA and reveals the existence of two subclusters within pJIA, regardless the positivity of rheumatoid factor and anti-CCP, paving the way to precision medicine.